Surgical management of chronic calcific deposit resembling tendon sheath infection in the index finger: A rare case report and literature review - Guo, Deming; Yang, Jingjing; Liu, Xiaoning (Frontiers in Surgery, 2023)
Background Calcific tendonitis rarely occurs in the fingers, and it is easily misdiagnosed. Herein we describe the case of a patient with multiple calcific lesions within the flexor digitorum superficialis and the extensor digitorum tendons of the distal interphalangeal joints of the right index finger, and the surgical treatment of those lesions. Case presentation The patient was a 66-year-old man who reported pain and swelling in his right index finger for one year. He was diagnosed with chronic calcific tendonitis based on his symptoms and radiology images. He was successfully treated surgically, and histopathological examination confirmed the diagnosis. After one month, the patient had healed well, and there was no recurrence. Conclusions This is the first report of a patient suffering from chronic calcific tendonitis in a finger who failed conservative treatment and was successfully treated with surgery. The outcome demonstrates that surgical debridement can yield a good outcome in patients with chronic calcific tendonitis.